Britain and the Olympic Games, 1908-1920 - Harris, Luke J. author. aut Link
XI, 289 p.
Keywords: Britain and the Olympic Games, 1908-1920 focuses upon the presentation and descriptions of identity that are presented through the depictions of the Olympics in the national press. This book breaks Britain down into its four nations and presents the debates that were present within their national press.